INVESTIGATION OF THE IMPACT OF BOTTLING ON FUEL LOSSES IN AIRCRAFT TANKS - Бойченко, С. В.; Береговий, О. М.; Федорович, Л. А. (Proceedings of National Aviation University (archive), 2021)
The results of researches of fuel losses from evaporation in dynamic conditions are considered, a special device for bubbling fuel to simulate the pumping of fuel into the fuel tank system and study of evaporation losses under these conditions.